Material deprivation and leading causes of death by gender: evidence from a nationwide small area study. Issue 4 (1st April 2001) - Benach, J; Yasui, Y; Borrell, C; Sáez, M; Pasarin, M I
Abstract : STUDY OBJECTIVE: To investigate the association between material deprivation and 10 leading causes of death by gender. DESIGN: Small area cross sectional ecological study using two dimensions of material deprivation (Index 1 and Index 2) drawn from 1991 census and cause specific mortality data aggregated for 1987–1995. SETTING: 2218 small areas in Spain. MAIN RESULTS: Strong detrimental associations of two deprivation indices were found with top six leading causes of death for men and top seven leading causes of death for women, except breast cancer. For men, the highest percentages of excess mortality (between 40% and 60%) were found for smoking and alcohol related causes of death such as lung cancer, chronic obstructive pulmonary diseases, and cirrhosis while for women the highest percentages of excess mortality (between 40% and 60%) were found for diet related causes such as diabetes and ischaemic heart disease. CONCLUSIONS: Health inequality is a widespread phenomenon in the majority of the top leading causes of deaths of the nation. Increasing levels of deprivation indices are associated with mortality risk differently by both cause and gender. Results suggest that deprivation effects mainly captured by Index 2 may manifest largely as unfavourable health behaviours leading to gender specific sets of causes of deaths. Findings of this study are consistent with the idea that material deprivation determines health inequality through both an increase of general susceptibility to ill health, leading to excess mortality in a wide range of causes, and a set of specific factors, resulting in an increased risk of death from a specific set of causes in each gender.